2008
DOI: 10.1002/app.28247
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel benzoxazine precursor containing phenol hydroxyl groups and its polymer

Abstract: A novel benzoxazine precursor containing phenol hydroxyl groups was synthesized from bisphenol A, 4,4 0 -diaminodiphenyl methane, and formaldehyde with a molar ratio of 2:1:4. The benzoxazine precursor was characterized with Fourier transform infrared, proton nuclear magnetic resonance, and size exclusion chromatography. The curing reaction was monitored by the gel time, differential scanning calorimetry, and Fourier transform infrared. The obtained polybenzoxazine showed high thermal stability and a high glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…It complied that HPPE terminated with phenolic hydroxyl groups had catalyzed the curing reaction. This was in good agreement with the past studies reported by Men et al [20] …”
Section: Curing Reaction Of Ba/13-pbo/hppe Resinssupporting
confidence: 94%
See 1 more Smart Citation
“…It complied that HPPE terminated with phenolic hydroxyl groups had catalyzed the curing reaction. This was in good agreement with the past studies reported by Men et al [20] …”
Section: Curing Reaction Of Ba/13-pbo/hppe Resinssupporting
confidence: 94%
“…The effect of hyperbranched polymers on the flame retardant properties of benzoxazine resins was seldom reported. Since phenolic hydroxyl groups could catalyze the ring-opening reaction of benzoxazine resins and react with 1,3-PBO, [20] in this paper, a new reactive hyperbranched polyphosphate ester (HPPE) terminated with phenolic hydroxyl groups was synthesized and used to modify benzoxazine-1, 3-PBO resins. The curing reaction, thermal and flame retardant properties of the modified resins were investigated in details.…”
Section: Introductionmentioning
confidence: 99%
“…Of these two approaches, the majority of polybenzoxazine research published today has focused on materials in which the multifunctional core is provided by the phenolic compound. Multifunctional amine based polybenzoxazines have an enormous potential in tailoring molecule structure for specific applications and benzoxazines based on difunctional [6][7][8][9], multifunctional aromatic diamines or their derivatives [10] have been discussed in the literature. Recently aromatic diamine-based benzoxazines, which could not easily be synthesized by traditional approaches, were prepared by a three-step procedure [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Various functional groups such as cyano, [11][12][13][14] allyl, 7,[15][16][17][18] acetylene, [19][20][21][22] aldehyde, 23,24 carboxyl, 25,26 and hydroxyl 27,28 have been introduced into benzoxazines, and the properties of the corresponding polybenzoxazines were improved to varying degrees.…”
Section: Introductionmentioning
confidence: 99%